Assembled Female Identities in Neo-Victorian Asylum Narratives. - Pettersson, Lin Elinor (My University, 2024)
In the twenty-first century, women writers in particular have explored the aesthetic possibilities of neo-Victorian asylum fiction to delve into issues of gender and sexuality, and challenged tenacious patriarchal and heteronormative frames. Neo-Victorian asylum narratives bear on the historical context of the development of psychiatry and psychology into separate branches of medical science, which “did not occur in a national vacuum”; rather, theories regarding mental states and disorders developed in a multifaceted and intertwined intellectual context of European schools of psychiatry in the nineteenth century (Jansson 2021, 10). Moreover, “the term ‘Victorian psychology’ is potentially misleading”, since it “was not a coherent discipline, but rather a collection of works by writers who drew upon philosophy, social theory, evolutionary theory, physiology, neurology, alienism, and psychiatry” (Vrettos 2005, 69). Neo-Victorian asylum fiction builds on Victorian literary legacies and echoes sensationalist literature, gothic imagery and tropes of madness – as such, it is an entangled territory where different disciplines, multiple discourses and texts intersect across time in ways that fit the notion of assemblage. Taking this as a starting point, I will introduce Assemblage Theory as a critical tool to analyse assembled and entangled identities and reading practices in neo-Victorian asylum narratives drawing mainly on Deleuze and Guattari’s conceptualisation of assemblage in A Thousand Plateaus (1980), and as explained by Nail in “What Is an Assemblage?” (2017). My main aim is to examine the neo-Victorian asylum as assembled through a set of ongoing relational processes that intersect in productive ways and to analyse how the female body becomes a focal point where disciplinary technologies of power operate.
Keywords: Steampunk (Movimiento); Persona (Filosofía); Neo-Victorian asylum fiction; Female Asylum Patients; Assemblage theory; Feminist historical fiction; Entangled identities; Entangled bodies